Synthesis of Hydroxyapatite-Zirconia Composite and Activity Test as Dental Implant Material - Noviyanti, Atiek Rostika; Yashfi, Difa Muhammad; Deawati, Yusi; Maryani, Eneng; Hemzah, Sabila Aulia; Ma’amor, Azman (Chimica et Natura Acta, 2025)
Hydroxyapatite (HAp) is one of the bioceramics that is widely used in various fields, one of which is the health sector as a dental implant material. One of the reasons is that hydroxyapatite has good biocompatibility. In this study, natural calcium sources such as eggshell waste were utilized for the synthesis of hydroxyapatite. However, its mechanical properties do not yet meet the requirements as a dental implant material, its modification is usually done by adding other compounds, such as zirconium oxide. Zirconium oxide can be used as a support material because it has good strength, toughness, and durability as a dental implant. Therefore, in this study, a hydroxyapatite-zirconium oxide (HAp-ZrO2) composite was synthesized for dental implant material. This study aims to determine the effect of adding ZrO2 on increasing the mechanical and corrosion resistance of HAp. The research methods include isolation of CaO from chicken eggshells, synthesis of hydroxyapatite, synthesis of HAp-ZrO2 composite, hardness test, and corrosion resistance test. Based on SEM images, the addition of ZrO2 can reduce the level of HAp agglomeration. The addition of ZrO2 to HAp did not significantly affect the increase in HAp hardness since the zirconia phase formed is possibly dominated by the cubic phase. The optimum HAp-ZrO2 composite was obtained with a variation of HAp-90%-ZrO2-10% which showed the highest crystallinity of 75.37% with a crystal size at 10.15 nm with corrosion resistance comparable to pure HAp.